Root morphological and physiological traits and arbuscular mycorrhizal fungi shape phosphorus-acquisition strategies of 12 vegetable species - Pu, Zitian; Zhang, Ruifang; Wang, Hong; Li, Qingyun; Zhang, Jianheng; Wang, Xin-Xin (Frontiers in Plant Science, 2023)
Trait plasticity and integration mediate vegetable adaptive strategies. However, it is unclear how patterns of vegetables in root traits influence vegetable adaptation to different phosphorus (P) levels. Nine root traits and six shoot traits were investigated in 12 vegetable species cultivated in a greenhouse with low and high P supplies to identify distinct adaptive mechanisms in relation to P acquisition (40 and 200 P mg kg-1 as KH2PO4). At the low P level, a series of negative correlations among root morphology, exudates and mycorrhizal colonization, and different types of root functional properties (root morphology, exudates and mycorrhizal colonization) respond differently to soil P levels among vegetable species. non-mycorrhizal plants showed relatively stable root traits as compared to solanaceae plants that showed more altered root morphologies and structural traits. At the low P level, the correlation between root traits of vegetable crops was enhanced. It was also found in vegetables that low P supply enhances the correlation of morphological structure while high P supply enhances the root exudation and the correlation between mycorrhizal colonization and root traits. Root exudation combined with root morphology and mycorrhizal symbiosis to observe P acquisition strategies in different root functions. Vegetables respond highly under different P conditions by enhancing the correlation of root traits. Low P supply could significantly improve the direct and indirect ways of mycorrhizal vegetable crops’ root traits axis on shoot biomass, and enhance the direct way of non-mycorrhizal vegetable crops’ root traits axis and reduce the indirect way of root exudates.